2019
DOI: 10.1101/19005611
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A deep learning approach with event-related spectral EEG data in attentional deficit hyperactivity disorder

Abstract: Attention deficit hyperactivity disorder (ADHD) is a heterogeneous neurodevelopmental disorder that affects 5% of the pediatric and adult population worldwide. The diagnosis remains essentially clinical, based on history and exam, with no available biomarkers. In this paper, we describe a deep convolutional neural network (DCNN) for ADHD classification derived from the time-frequency decomposition of electroencephalography data (EEG), particularly of event-related potentials (ERP) during the Flanker Task colle… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Similarly, using the ABIDE dataset, which was based on rs-fMRI and deep neural network, ASD was distinguished from typically developing subjects [71]. Wireless Communications and Mobile Computing In addition, it was found that CNN algorithm was most efficient among all applied ML algorithms, and several studies have reported the rise in accuracy for ADHD diagnosis and examination by utilizing CNN with an accuracy range of between 90 ± 10 percent [55,[72][73][74][75][76][77][78]. Similarly, numerous studies were also conducted using CNN for ASD diagnosis and analyses showing a high accuracy rate > 70-90% [44,[79][80][81][82].…”
Section: Recent Machine Learning and Deep Learning Softwarementioning
confidence: 99%
“…Similarly, using the ABIDE dataset, which was based on rs-fMRI and deep neural network, ASD was distinguished from typically developing subjects [71]. Wireless Communications and Mobile Computing In addition, it was found that CNN algorithm was most efficient among all applied ML algorithms, and several studies have reported the rise in accuracy for ADHD diagnosis and examination by utilizing CNN with an accuracy range of between 90 ± 10 percent [55,[72][73][74][75][76][77][78]. Similarly, numerous studies were also conducted using CNN for ASD diagnosis and analyses showing a high accuracy rate > 70-90% [44,[79][80][81][82].…”
Section: Recent Machine Learning and Deep Learning Softwarementioning
confidence: 99%
“…In recent years there have been several investigations into the removal of this artefact in the EEG by applying post-collection signal processing to the raw EEG data [7][8][9][10][11][12][13][14][15][16][17]. There have also been investigations into the properties of the tACS artefacts [18][19][20][21][22], for example how they spread across the head [19] and how they mix with other bio-signals such as ECG and breathing patterns [18].…”
Section: Introductionmentioning
confidence: 99%